Analisis Peran Pengadilan Pajak dalam Optimalisasi Pendapatan Negara - Irwan Triadi; Evi Fitriani (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The Tax Court has a crucial role in resolving tax disputes and optimizing state revenues. This study aims to analyze the effectiveness of the Tax Court in providing legal certainty for taxpayers and identifying obstacles that hinder its role in the Indonesian taxation system. The method used is a normative legal approach with an analysis of laws and regulations, court decisions, and related empirical data. The results of the study indicate that the dualism of guidance between the Supreme Court and the Ministry of Finance creates the potential for a conflict of interest that can affect the independence of judges in deciding tax disputes. In addition, limited access to the Tax Court, which is only located in Jakarta, causes obstacles for taxpayers in the regions to obtain justice quickly and efficiently. The policy of administrative sanctions in the form of a 100% fine for taxpayers whose appeals are rejected is also considered disproportionate and contrary to the principle of tax justice. To improve the effectiveness of the Tax Court, institutional reform is needed by unifying guidance under the Supreme Court, establishing Tax Court branches in various regions, and revising regulations related to tax sanctions in order to improve taxpayer compliance and trust in the national taxation system.